Effect of Spirulina Intervention on Oxidative Stress, Antioxidant Status, and Lipid Profile in Chronic Obstructive Pulmonary Disease Patients. (22nd January 2015) - Ismail, Md.; Hossain, Md. Faruk; Tanu, Arifur Rahman; Shekhar, Hossain Uddin
Abstract : Background and Objective. Oxidative stress is intimately associated with many diseases, including chronic obstructive pulmonary disease (COPD). Study objectives include a comparison of the oxidative stress, antioxidant status, and lipid profile between COPD patients and controls and evaluation of the effect of spirulina intervention on oxidative stress, antioxidant status, and lipid profile of COPD patients. Methods. 30 patients with COPD and 20 controls with no respiratory problems were selected. Global Initiative for Chronic Obstructive Lung Disease criteria were served as the basis of COPD diagnosis. The serum content of malondialdehyde (MDA), lipid hydroperoxide, glutathione (GSH), vitamin C, cholesterol, triglyceride (TG), and high density lipoprotein (HDL) was measured. The activity of superoxide dismutase (SOD), catalase (CAT), and glutathione-s-transferase (GST) was also measured. Two different doses, (500 × 2) mg and (500 × 4) mg spirulina, were given to two groups, each of which comprises 15 COPD patients. Results. All targeted blood parameters have significant difference ( P = 0.000 ) between COPD patients and controls except triglyceride (TG). Spirulina intake for 30 and 60 days at (500 × 2) mg dose has significantly reduced serum content of MDA, lipid hydroperoxide, and cholesterol ( P = 0.000 ) while increasing GSH, Vit C level ( P = 0.000 ), and the activity of SOD ( P = 0.000 ) and GST ( P = 0.038 ) . At the same time, spirulina intake for 30 and 60 days at (500 × 4) mg dose has favorable significant effect ( P = 0.000 ) on all targeted blood parameters except for HDL ( P = 0.163 ) .